Community empowerment strategy and its impact on economic improvement in Kalipucang Wetan Village, Batang Regency in 2021 - Hidayat Miftahuddin (Journal of Islamic Economics, Management, and Business (JIEMB), 2021)
Purpose – This study aims to investigate to what extent the public economy empowerment strategies are applied by KUB Batik Tulis Rifaiyah and what are the implications of the public economy empowerment used by KUB Batik Tulis Rifaiyah.Method – This research used the descriptive qualitative method. The study subject is community leaders, batik artisans, caretakers/communities, and related parties. The object of his research is KUB Batik Tulis Rifaiyah Kalipucang Wetan Batang. The data were analysed by using the technique of analysis and interactive model of analysis comprising data gathering, data grouping, and data display.Result – The results of this study indicate that empowerment in Kalipucang Wetan Batang Village has not been fully successful because of a lack of participation from the community. Implication – This research was made as a material for consideration and evaluation so that community empowerment in Kalipucang Wetan Village is getting better.Originality – The originality of this research lies in the object under study, analysis, and research location.